Responsive Information generation system for Kanhan River, an effective information system for river modeling - Lingote, Dinesh A; Katkar, Girish S; Vijay, Ritesh; Biniwale, R.B (International Journal of Computer Sciences and Engineering, 2018)
River is main source of water for drinking and domestic usage. Over exploitation and discharge of surface water in river stream has ecologically stressed the rivers. In view to manage river health, it is essential to carry out river engineering periodically. River follows complex structure; goes through dense forest and valleys. Therefore, measuring water quality and several other parameters associated with the river is a discouraging job. Mostly river follows longest path and generating data for such large geographical area is very challenging. Scientific study of the river requires data for several consecutive years. Having such large data requirement and expecting data generation simply through field-work is highly burdened and never ending process. Therefore, in this paper we introduced auto data generation techniques like: data extraction, data generation through public-partnership, data estimation and data generation using GIS (Geographic information system) based utility software. Lastly, we illustrate complete data generated by using these auto data generation techniques.